European Heart Rhythm Association (EHRA)/Heart Rhythm Society (HRS)/Asia Pacific Heart Rhythm Society (APHRS)/Latin American Heart Rhythm Society (LAHRS) expert consensus on arrhythmias and cognitive function: what is the best practice?. Issue 9 (18th March 2018) - Dagres, Nikolaos; Chao, Tze-Fan; Fenelon, Guilherme; Aguinaga, Luis; Benhayon, Daniel; Benjamin, Emelia J; Bunch, T Jared; Chen, Lin Yee; Chen, Shih-Ann; Darrieux, Francisco; de Paola, Angelo; Fauchier, Laurent; et al.
Abstract: